Role of insects in the transmission of banana bacterial wilt - Tinzaara, William; Gold, C.; Ssekiwoko, F.; Tushemereirwe, Wilberforce K.; Bandyopadhyay, Ranajit; Abera, A.; Eden-Green, S. (2007)
The banana bacterial wilt caused by the Xanthomonas campestris pv. musacearum (Xcm) is one of the major constraints to banana production in Uganda. Field observations suggest that the primary means of disease spread is by insect transmission through the male flowers. This study carried out an inventory of insects found on banana inflorescence, investigated possible sources of inoculum in banana plants and determined insect species that carried the bacterium on their bodies and thus possible vectors of the disease. The most abundant insects visiting banana flowers are stingless bee. Plebeina denoiti (Vachal) (Apidac), fruit flies (Drosophilidae) and grass flies (Chloropidae). Female flowers had twice as many insects as male flowers. The bacterial cells have been isolated from the stingless bee (P. denoiti), honey bees ( Apis melifera ), fruit flies and grass flies that had been collected from male flowers of both asymptomatic and symptomatic plants. The bacterial cells isolated from P. denoiti were more than two times as many as other insect groups. Further studies to confirm the most of transmission by insects, and to investigate transmission epidemiology and biology of banana Xanthomonas wilt have been initiated.